Brief Review of the Role of Glycogen Synthase Kinase-3β in Amyotrophic Lateral Sclerosis. (14th February 2011) - Koh, Seong-Ho; Baek, Wonki; Kim, Seung H.
Abstract : Glycogen synthase kinase-3 β (GSK-3 β ) is known to affect a diverse range of biological functions controlling gene expression, cellular architecture, and apoptosis. GSK-3 β has recently been identified as one of the important pathogenic mechanisms in motor neuronal death related to amyotrophic lateral sclerosis (ALS). Therefore, the development of methods to control GSK-3 β could be helpful in postponing the symptom progression of ALS. Here we discuss the known roles of GSK-3 β in motor neuronal cell death in ALS and the possibility of employing GSK-3 β modulators as a new therapeutic strategy.